Institutionalized Organizations: Formal Structure as Myth and Ceremony - John Meyer; Brian Rowan (Journal of Economic Sociology, 2011)
Many formal organizational structures arise as reflections of rationalized institutional rules. The elaboration of such rules in modern states and societies accounts in part for the expansion and increased complexity of formal organizational structures. Institutional rules function as myths which organizations incorporate, gaining legitimacy, resources, stability, and enhanced survival prospects. Organizations whose structures become isomorphic with the myths of the institutional environment-in contrast with those primarily structured by the demands of technical production and exchange-decrease internal coordination and control in order to maintain legitimacy. Structures are decoupled from each other and from ongoing activities. In place of coordination, inspection, and evaluation, a logic of confidence and good faith is employed.